The Genotype-Phenotype Association of Von Hipple Lindau Disease Based on Mutation Locations: A Retrospective Study of 577 Cases in a Chinese Population - Qiu, Jianhui; Zhang, Kenan; Ma, Kaifang; Zhou, Jingcheng; Gong, Yanqing; Cai, Lin; Gong, Kan (Frontiers in Genetics, 2020)
Von Hippel-Lindau (VHL) disease is a hereditary kidney cancer syndrome, with which patients are more likely to get affected by renal cell carcinoma (RCC), pancreatic cyst or tumor (PCT), central nervous system hemangioblastoma (CHB), retinal angiomas (RA) and pheochromocytoma (PHEO). Mutations of VHL gene located in 3p25 may impair the function of the VHL protein and lead to the disease. It’s confusing why obvious phenotype varieties exist among VHL patients. Here we aimed to ascertain whether the mutation types and locations affect the phenotype. We enrolled 577 Chinese VHL patients from 211 families and divided them into 3 groups and 6 subgroups according to their mutation types and locations. Cox survival analysis and Kaplan–Meier analysis were used to compare intergroup age-related tumor risks. Patients with nonsense or frameshift mutations that were located before residues 117 of VHL protein (NoF1 subgroup) hold lower age-related risks of VHL associated tumors (HR=0.638, 95%CI 0.461-0.883, p=0.007), CHB (HR=0.596, 95%CI 0.409-0.868, p=0.007) or PCT (HR=0.595, 95%CI 0.368-0.961, p=0.034) than patients whose mutations were located after residues 117 (NoF2 subgroup). Patients in NoF1 subgroup still had lower age-related risks of CHB (HR=0.652, 95%CI 0.476-0.893, p=0.008) and PCT (HR=0.605, 95%CI 0.398-0.918, p=0.018) compared with those in combined NoF2 subgroup and other truncating mutation patients. NoF1 subgroup correspondingly had a longer estimated median lifespan (64 yr vs 55 yr, p=0.037) than NoF2 subgroup. Among patients with missense mutations of VHL, only a small minority (23 of 286 missense mutations carriers) carried mutations involving neither HIF-α binding region nor elongin C binding region, who were grouped in MO subgroup. MO subgroup seemed to have a higher age-related risk of PHEO. In the whole cohort (n=577), PHEO was an independent protective factor for CHB (p=0.001) and survival (p=0.005). RA and CHB failed to predict the age-related risk of each other. The mutation types and locations of VHL gene are associated with phenotypes. Genetic counselors could predict phenotypes more accurately based on more detailed genotype-phenotype correlations. Further genotype-phenotype studies should focus on the prediction of tumor recurrence, progression and metastasis. The deep molecular mechanism of genotype-phenotype correlation is worth further exploring.